Iron: essential for life and a source of diseases - Gutiérrez, Lucia (2015)
Iron is a fundamental element for life, being essential in vital processes such as oxygen transport, electron transfer, enzymatic reactions, aerobic metabolism, photosynthesis or nitrogen fixation. Given the relevance of this element in metabolic routes central to life development, it is unsurprising that a great number of pathologies are linked to iron metabolism problems. Iron pathological species that appear in the frame of some diseases are nanometric materials, whose characterization presents huge difficulties. Detailed knowledge of these species may have great relevance in different problems such as the improvement of malaria diagnostic techniques or the treatment of neurodegenerative diseases.